Effect of Adding 3% Chitosan, 2.5% Neem, and 0.5% Sodium Metabisulphite on Anti-microbial and Mechanical Properties of Heat Activated Denture Base Resin- An In Vitro Study - Boobalan, Pavithra; Nair, Vivek V; G, Mithu M (Bangladesh Journal of Medical Science, 2026)
Background Denture stomatitis, commonly linked to microbial colonization on denture surfaces, remains a persistent challenge in prosthodontics. Incorporating antimicrobial agents into denture base resin represents a promising strategy to combat this condition while maintaining essential mechanical properties. The study evaluated the antimicrobial efficacy, flexural strength, and impact resistance of heat-activated denture base resin modified with chitosan, neem, and sodium metabisulphite. Methodology A total of 160 samples were fabricated and allocated to four groups: Group 1 (control), Group 2 (3% chitosan), Group 3 (2.5% neem), and Group 4 (0.5% sodium metabisulphite). Each group was categorized into four subgroups, with 10 samples in each subset. Antimicrobial activity was assessed by counting colonyforming units (CFUs). Flexural strength (MPa) was determined with a universal testing machine, while impact strength (kJ/m²) was assessed using a Charpy impact tester. Data was analysed using the Kruskal-Wallis test with post-hoc comparisons, and results were considered significant at p < 0.05. Results All experimental groups exhibited reduced CFU counts. Chitosan and neem groups demonstrated statistically significant antimicrobial activity (p < 0.001), whereas sodium metabisulphite exhibited a limited effect. Flexural strength was reduced in the chitosan and neem groups, but it was not altered in the sodium metabisulphite group. No significant differences in impact strength were observed (p = 0.224). Conclusion Natural antimicrobials like chitosan and neem effectively enhance the antimicrobial performance of denture base resins, though with some compromise in flexural strength. Sodium metabisulphite, while mechanically stable, lacks strong antimicrobial potency. These findings highlight the potential of bioactive additives for functional improvement of denture materials, with implications for the prevention of denture-related infections. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S137-S145